Priorities for Russian Education System Reformation - Malganova, Irina; Saralinova, Dzhamilya; Dokhkilgova, Diba (Journal of History Culture and Art Research, 2018)
In the modern conditions of the knowledge economy, when professional knowledge becomes obsolete quickly, the increased attention of the state to the sphere of education is noted. Accordingly, it is necessary to revise the approaches to the management of education sphere in the long term. The prerequisites for education sphere reformation in Russia were the transformational processes of the social reorganization of the Russian state. An effective organization of the education system in modern conditions is the basis for an economic growth achievement. Therefore, it is necessary to apply new principles for the training of professional personnel, taking into account the needs of the emerging innovative market economy. The sphere of education as one of the most important aspects of society life is in the joint responsibility of the federation and its subjects. At the federal level, they determine the vector and the main priorities for the development of the state educational system, at the regional level they develop the main ideas of federal policy taking into account regional peculiarities, needs and opportunities. The standard of living and well-being of Russian society, its general economic and social development, the level and the pace of scientific and technical achievements are determined by the level and the quality of the state educational system operation. Besides, the structure and the content of the education system itself, its competitiveness in the world arena, the compliance with international quality standards and requirements, determine the level of innovative development of the country economy, the intensification of economic development, a favorable social atmosphere and the national security at the international, national and regional levels.